Genome-Wide Association Analysis of Grain Size Traits in a Global Barley (Hordeum vulgare L.) Collection - Bouhlal, Outmane; Sanchez-Garcia, Miguel; Moulakat, Adil; Rachdad, Fatima Ezzahra; Hiddar, Houda; Kehel, Zakaria; Kandil, Mostafa; Visioni, Andrea (2024)
Presentation on Genome-Wide Association Analysis of Grain Size Traits in a Global Barley (Hordeum vulgare L.) Collection.